Integrating science and soul in education: the lived experience of a science educator bringing holistic and integral perspectives to the transformation of science teaching - Stack, Sue (Curtin University, 2006)
This is an auto-ethnographic study into the lived experience of a science teacher as she attempts to transform her science teaching practice and the practice of other science teachers over a period of 15 years. In exploring what it means to be a holistic educator she is faced with disorienting dilemmas which cause her to question underpinning assumptions, values and curriculum frameworks which inform traditional science teaching practice and culture. In trying to reconcile science and soul in the pedagogical space of a physics classroom her journey requires a deep investigation of self in various cultures – science culture, educational culture, modernist and postmodernist cultures.Part 1 of the study introduces the key referents of Integral Theory, Holistic Education and Spirituality which she used to inform her changing education practice. Part 2 reflects on her journey from a traditional constructivist classroom, into ones which explore meaning, questioning, significance, discourse, ethics and enabling frameworks.Part 3 concludes with an attempt to integrate science and soul into a vision for science educators. This includes a model which suggests that science has various development stages or cultures and that science teaching can be strategically aligned to facilitate the growth of human consciousness.